METHODOLOGY OF TEACHING ENGLISH TO PRESCHOOL CHILDREN - Boboyeva Sarvinoz (Academia Science Repository, 2023)
In this article, based on the necessity of teaching English to children of preschool age, the advantages of teaching a foreign language from the preschool age are discussed, and the most modern and effective methods of teaching a foreign language to children of preschool age are discussed. comments about the possibilities of using game technology, information communication tools are presented.